NGC 6251 at multiple scales and wavelengths - Werner, P; Worrall, D; Birkinshaw, M (2002)
We have studied the FRI radio galaxy NGC 6251 and its environment at several wavelengths and scale lengths. On the large scale, we have probed the gravity field by measuring the velocity dispersion of the cluster members associated with NGC 6251 and relating this to, the cluster's X-ray emission. On the small scale, the gravitational information is provided by cold HI near the nucleus and the distribution of stars and gas near the centre of the galaxy. The cold HI gas which we have measured explains the absorption of the central X-ray emission and is consistent with the extinction through the recently discovered HST gas disc of NGC 6251.